2019
DOI: 10.1101/596783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rs6505162 C>A polymorphism in themiRNA-423gene exhibits a protective element of coronary artery in a southern Chinese population with Kawasaki disease

Abstract: BackgroundManifesting as acute rash, fever and vasculitis, belonging to autoimmune syndrome, Kawasaki disease(KD) is prone to occur in infants and young children. Males and females is affected by KD at a ratio of 1.4 to 1.7: 1. KD is known to own many common clinical manifestations and complications, like coronary artery lesion(CAL) and coronary artery aneurysm(CAA). Polymorphisms of the rs6505162 locus in themiRNA-423gene are associated with enhancive susceptibility to coronary artery disease and the alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Other studies have identified the association of rs6505162 C/A with the risk of Esophageal Squamous Cell Carcinoma [58]. Although rs6505162 C/A is not situated in the seed region of the mature miRNAs, it has been proposed that rs6505162 C/A can alter not only the mature miR-423 expression [59] ( Zhao et al, 2015), but it may also modulate its targeting efficiency [19]. Other studies have shown that the CA/AA genotypes of rs6505162 C/A could reduce the occurrence of artery aneurysms [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have identified the association of rs6505162 C/A with the risk of Esophageal Squamous Cell Carcinoma [58]. Although rs6505162 C/A is not situated in the seed region of the mature miRNAs, it has been proposed that rs6505162 C/A can alter not only the mature miR-423 expression [59] ( Zhao et al, 2015), but it may also modulate its targeting efficiency [19]. Other studies have shown that the CA/AA genotypes of rs6505162 C/A could reduce the occurrence of artery aneurysms [59].…”
Section: Discussionmentioning
confidence: 99%
“…Although rs6505162 C/A is not situated in the seed region of the mature miRNAs, it has been proposed that rs6505162 C/A can alter not only the mature miR-423 expression [59] ( Zhao et al, 2015), but it may also modulate its targeting efficiency [19]. Other studies have shown that the CA/AA genotypes of rs6505162 C/A could reduce the occurrence of artery aneurysms [59]. The rs6505162 C/A is reported to have a role in different diseases including Type 2 Diabetes.…”
Section: Discussionmentioning
confidence: 99%